Emphysematous pyelonephritis - Is surgery necessary?. (November 2017) - Butler, Joseph; Bhatt, Ree'Thee; Amante, Gionathan
Abstract : Introduction: Emphysematous pyelonephritis is a rare, life threatening acute suppuration of the kidney, characterised by the presence of air in the renal parenchyma, sometimes extending to the surrounding tissue. E. Coli and Klebsiella are the most common causative organisms, but the exact pathogenesis is poorly understood. It carries a high mortality, cited up to 50% and therefore requires prompt diagnosis and management. Case description: A 52-year old woman presented to A&E with a two day history of severe left-sided abdominal pain, rigors, vomiting and increased urinary frequency. Her past medical history was significant for non-insulin dependent Type 2 diabetes mellitus, a well-established risk factor that is present in 90% of cases. On examination, she had marked left flank tenderness, tachycardia and pyrexia. Bloods showed raised inflammatory markers with a severe AKI. Results and Conclusions: A CT KUB carried out in A&E showed air bubbles in the parenchyma and calyceal system of the left kidney, which confirmed emphysematous pyelonephritis. As there was no obstruction, the decision was made to manage conservatively. She was started on intravenous empiric metronidazole and tazocin, aggressive fluid resuscitation and close monitoring of her blood glucose. On day 3, initial blood cultures grew ESBL and tazocin was switched to meropenem and amikacin. A repeat CT scan on day 4 showed complete resolution of the parenchymal gas. Nonetheless, she continued to have recurrent pain and pyrexia. She stayed in hospital for a total of 16 days, with conservative management alone significantly improving her AKI and pyelonephritis. She was discharged with analgesia for residual loin tenderness. Take home message: As portrayed in this case, young diabetic women are predisposed to developing emphysematous pyelonephritis. Nephrectomy remains the treatment of choice in most patients, whilst nephrostomy drainage is required in patients with urinary obstruction. Systematic reviews have indicated that antibiotic therapy with nephrostomy carries a reduced mortality risk in comparison to antibiotic therapy with emergency nephrectomy, though there are currently no guidelines available to optimally manage the condition. Prompt CT diagnosis and targeted antibiotic therapy in the initial assessment of this patient were crucial in preventing her from having to undergo an invasive surgical procedure.